1987
DOI: 10.1055/s-2007-1011846
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Nocturnal Plasma Melatonin and 6-Sulphatoxymelatonin by Bright and Dim Light in Man

Abstract: Previous studies have shown that bright light (2500 lux) suppresses nocturnal secretion of melatonin, while dim light (500 lux) has little or no effect. We have studied the effect of varying intensities of light on 5 normal male volunteers (age 18-28). The experiment was divided into 3 parts which took place at weekly intervals. Subjects remained under artificial light (fluorescent strip 150-250 lux) between 2000 h-2300 h, they then retired to bed in darkness. On each occasion, between 0030 h and 0100 h, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(89 citation statements)
references
References 0 publications
4
85
0
Order By: Relevance
“…More recent studies have investigated the relationship between light intensity and melatonin suppression. Whilst some researchers have reported no differences in melatonin response to varying light intensities (1000 lux and 2500 lux) (Boyce and Kennaway 1987), more recent reports have suggested that humans are sensitive to lower levels of light (300 lux) (Bojkowski et al 1987). McIntyre et al (1989a) also reported a response to low levels of light and suggested an intensity dependent relationship between light and percentage of nocturnal melatonin suppression (3000, 1000, 500, 350, and 200 lux), with no gender differences (Nathan et al unpublished observations).…”
mentioning
confidence: 99%
“…More recent studies have investigated the relationship between light intensity and melatonin suppression. Whilst some researchers have reported no differences in melatonin response to varying light intensities (1000 lux and 2500 lux) (Boyce and Kennaway 1987), more recent reports have suggested that humans are sensitive to lower levels of light (300 lux) (Bojkowski et al 1987). McIntyre et al (1989a) also reported a response to low levels of light and suggested an intensity dependent relationship between light and percentage of nocturnal melatonin suppression (3000, 1000, 500, 350, and 200 lux), with no gender differences (Nathan et al unpublished observations).…”
mentioning
confidence: 99%
“…Our data suggest that ambient light intensity may also be a factor masking the endogenous rhythm in humans. Although the intensity of light found here to affect temperature was high, others have reported behavioral and physiological effects with much lower levels (e.g., Bojkowski et al, 1987;Boyce & Kennaway, 1987;Czeiler et al, 1989;McIntyre et al, 1989;Moore-Ede, Sulzman, Fuller, 1982;Sulzman, Fuller, & Moore-Ede, 1979). Thus, a prudent approach suggests that ambient light intensity be considered another possible factor 153 masking the endogenous temperature rhythm.…”
Section: Sleepiness (Mwt) Under Continuous Bl -Dl Conditionsmentioning
confidence: 60%
“…Specifically we asked "Will nighttime exposure to light intensities sufficient to suppress melatonin synthesis reduce sleepiness and enhance nighttime alertness and performance levels during sustained wakefulness?" We should note at the outset that we did not assay melatonin levels but, instead, used a light intensity found repeatedly to suppress nighttime melatonin to near daytime levels (Bojkowski, et al, 1987;Lewy et al, 1980;McIntrye et al, 1989). A second question relates to nighttime body temperature.…”
Section: Reaction Timementioning
confidence: 99%
“…Its production is under the circadian control of the master circadian oscillator localized in the hypothalamic suprachiasmatic nucleus. Th e melatonin production in the night can be eff ectively suppressed by a light (Bojkowski et al 1987a;McIntyre et al 1989). Th e suppressive eff ect of the light depends on its duration, intensity, and wavelength.…”
mentioning
confidence: 99%